HIV/AIDS, human capital, and economic prospects for Mozambique - Arndt, Channing (International Food Policy Research Institute, 2002)
As in other countries in the southern Africa region, a human development catastrophe is unfolding in Mozambique. Recently released data estimate HIV prevalence rates amongst the adult population in the year 2000 at around 12% with substantial regional variation. Due to the magnitude of the HIV/AIDS pandemic, it has become a top priority development issue. The goal of this paper is to try to come to grips with the economic dimensions of the pandemic. In this initial assessment, the focus is on implications for macroeconomic prospects. Particular attention is paid to human capital accumulation. Taking demographic projections, human capital accumulation projections, and other inputs, a recursive computable general equilibrium approach is employed to quantify impacts on key macroeconomic variables and identify the major channels through which these impacts occur. Policy options for blunting the major negative impact channels are also considered.